2019
DOI: 10.1007/s40266-019-00662-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Symptomatic Slow-Acting Drugs for Osteoarthritis: Outcomes of a Systematic Review and Meta-Analysis

Abstract: Background Symptomatic slow-acting drugs for osteoarthritis (SYSADOAs) are an important drug class in the treatment armamentarium for osteoarthritis (OA). Objective We aimed to re-assess the safety of various SYSADOAs in a comprehensive meta-analysis of randomized placebo-controlled trials, using, as much as possible, data from full safety reports. Methods We performed a systematic review and random-effects meta-analyses of randomized, double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
24

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 97 publications
1
49
0
24
Order By: Relevance
“…Both glucosamine and CS can be considered as safe treatments for patients with OA. A recent systematic review and meta-analysis found no statistically significant increase in odds between glucosamine or CS, each compared with placebo, for any system organ class (SOC)-related disorders including: GI, cardiac, vascular, nervous system, skin and subcutaneous tissue, musculoskeletal and connective tissue, and disorders of the renal and urinary systems [16]. In addition, no difference in odds for severe and serious AEs, and for withdrawals due to AEs was found for glucosamine or CS versus placebo.…”
Section: Sysadoasmentioning
confidence: 99%
See 1 more Smart Citation
“…Both glucosamine and CS can be considered as safe treatments for patients with OA. A recent systematic review and meta-analysis found no statistically significant increase in odds between glucosamine or CS, each compared with placebo, for any system organ class (SOC)-related disorders including: GI, cardiac, vascular, nervous system, skin and subcutaneous tissue, musculoskeletal and connective tissue, and disorders of the renal and urinary systems [16]. In addition, no difference in odds for severe and serious AEs, and for withdrawals due to AEs was found for glucosamine or CS versus placebo.…”
Section: Sysadoasmentioning
confidence: 99%
“…Diacerein has a small beneficial effect on OA pain; however, the safety of diacerein has been called into question. In a meta-analysis, the odds of any AE with diacerein was more than twice that of placebo (odds ratio [OR] 2.22, 95% CI 1.58, 3.13) [16]. This was largely due to increased odds of GI AEs with diacerein versus placebo (OR 2.85, 95% CI 2.02, 4.04), of which diarrhea, abdominal pain, soft stools, and colitis were frequently reported, and a high increase in odds of renal and urinary disorders with diacerein (OR 3.42; 95% CI 2.36, 4.96), urine discoloration being the most reported effect.…”
Section: Sysadoasmentioning
confidence: 99%
“…Recently, the ESCEO commissioned several systematic reviews and meta-analyses of randomized, placebo-controlled trials to reassess the safety of various anti-OA medications, including topical nonsteroidal anti-inflammatory drugs (NSAIDs), symptomatic slow-acting drugs for OA (SYSADOAs) and intra-articular hyaluronic acid (IAHA) [30][31][32]. For this purpose, the MEDLINE, Cochrane Central Register of Controlled Trials, and Scopus databases were comprehensively searched.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology and the outcomes of these systematic reviews have been extensively described in each manuscript. From the articles included in each systematic review, we collected information on how AE data were reported; details on how AE-related results were reported in each article retrieved from the systematic review processes can be found in the tables describing the characteristics of the included studies in each specific manuscript reporting the outcomes of these new meta-analyses (in this supplement) [30][31][32]. For the purpose of preparing the ESCEO recommendations for the reporting of harms in future manuscripts on trials on anti-OA medications, we summarized the ways in which harms-related data have been reported across the articles retrieved for these new ESCEO meta-analyses, and report here the common sub-standard harms reporting practices found in these prior manuscripts on RCTs on anti-OA drugs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation